(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Negative perception is a significant barrier to mathematical proficiency among tertiary students in West Africa. This study evaluates the impact of the Culturo-Techno-Contextual Approach (CTCA) on the cognitive and affective dispositions of 376 first-year students at the University of Makeni (UNIMAK), Sierra Leone. Findings from a quasi-experimental analysis demonstrate that CTCA significantly enhances student confidence, participation, and conceptual clarity. The study concludes that by centering instruction on the "Culturo-Techno" axis, educators can effectively dismantle "math anxiety" and improve academic performance.